Deep-space CubeSats: thinking inside the box. Issue 5 (1st October 2018) - Walker, Roger; Binns, David; Bramanti, Cristina; Casasco, Massimo; Concari, Paolo; Izzo, Dario; Feili, Davar; Fernandez, Pablo; Fernandez, Jesus Gil; Hager, Philipp; Koschny, Detlef; Pesquita, Vasco; et al.
Abstract : Roger Walker and colleagues consider the potential for sending nanospacecraft into deep space. Abstract : Roger Walker and colleagues consider the potential for sending nanospacecraft into deep space.